PENGARUH SELF ASSESSMENT SYSTEM, TINGKAT PENDIDIKAN, DAN PELAYANAN FISKUS TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK UMKM DI KOTA PEKANBARU - Maharani, Indah Sri; Kamaliah, Kamaliah; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to prove the self assessment system, level of education, and service tax authorities have a significant effect on the level of tax compliance UMKM. This study used a questionnaire distributed to as many as 99 copies of the UMKM in Pekanbaru. The statistical method used to test the hypothesis is multiple regression with the help of SPSS version 18.0. The results of this study provide evidence that influence self assessment system, the level of education, and service tax authorities have a significant effect on the level of tax compliance of the UMKM in Pekanbaru through multiple correlation coefficient (R) of 0.252 and its relationship low.Keywords : Self assessment system, level of education, service tax authorities, and tax payer compliance